Request a call back

Asked by kirtichawla94 | 12 Mar, 2010, 03:55: PM Expert Answer

2x + 3y -7 =0        ... (1)

(m-1)x - (m+y) = (3m-1)

(m-1)x - y = 3m-1+m

(m-1)x - y = 4m-1 .... (2)

We can write equation (1),

as 2x + 3y = 7

-2x/3 - y = -7/3

Comparing with (2), coefficients of y i.e. -1 in both equations, and if other coefficients are also same, then the given pair of equations will have inifinitely many solutions.

Hence, m-1 = -2/3,

m = 1/3 or

4m - 1 = -7/3

m = -1/3.

Regards,

Team,

TopperLearning.

Answered by | 13 Mar, 2010, 06:28: AM
CBSE 10 - Maths
Asked by hanugraha | 30 May, 2010, 07:53: PM ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by hanugraha | 30 May, 2010, 07:13: PM ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by 2806rahul | 30 May, 2010, 09:28: AM ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by shobhitdc | 29 May, 2010, 04:59: PM ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by ROJAAPPA | 29 May, 2010, 12:58: PM ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by shobhitdc | 29 May, 2010, 11:59: AM ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by shobhitdc | 29 May, 2010, 10:52: AM ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by devanshmudgal | 28 May, 2010, 07:31: PM ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by shobhitdc | 28 May, 2010, 01:12: PM ANSWERED BY EXPERT
CBSE 10 - Maths
Asked by shobhitdc | 28 May, 2010, 01:08: PM ANSWERED BY EXPERT